CAUSALITY MODEL OF CONSUMER PURCHASE INTENTION ON ENVIRONMENTALLY FRIENDLY PACKAGING BEVERAGE PRODUCTS - Muhammad Zulfiqar Mahmud; Widayat Widayat; Rahmad Wijaya (Manajemen Bisnis, 2020)
This study aims to construct a correlational model for the determinant of consumer purchase intention on environmentally friendly packaging beverage products by examining the product image and company reputation as mediators in the association of green perceived value on consumer purchase intention with the ex-post facto quantitative approach. The target population is the community in Malang City, EastJava who is aware of the existence of cardboard packaging beverage products and intends to purchase the products. Data were collected by employing a questionnaire distributed online. 300 respondents were selected by convenience sampling. The collected data were analyzed using Structural Equation Modeling (SEM) by utilizing AMOS software. The final model was obtained with an adequate Goodness of Fit value.The structural model that has been successfully constructed shows that green perceived value has no significant effect on purchase intention. Besides, the product image and company reputation play a role in mediating the impact of Green Perceived Value on Purchase Intention.